Polyfunctional T cells and unique cytokine clusters imprint the anti rAAV2/rAAV9 vector immune response - Holtkamp, Stephan J.; Lagoda, Florian R.; Lister, Adam; Harish, Pradeep; Kleymann, Ulrike; Pesch, Theresa; Soon, Chai Fen; Pirmohamed, Munir; Naisbitt, Dean; Trautwein, Mark (Frontiers in Immunology, 2024)
Polyfunctional T cells programmed to perform activities such as degranulation of lytic enzymes and simultaneous production of multiple cytokines are associated with more effective control of viral infections. Immune responses to recombinant adeno-associated virus (rAAV) vector delivery systems can critically influence therapeutic efficacy and safety of gene therapy. However, knowledge of polyfunctional T cells in anti-AAV immune responses is scarce. To bridge this knowledge gap, we have investigated the polyfunctionality of primary human CD4 T cells from healthy donors after in-vitro exposure to rAAV2 or rAAV9 vectors. By performing proliferation assays of co-cultured T cells and rAAV pulsed monocyte-derived dendritic cells from healthy donors we demonstrate T cell reactivity of 43% and 50% to rAAV2 and rAAV9 vectors, respectively. We validated this frequency in a second screen using another set of healthy donors measuring CD25 and CD71 T cell activation. Single T cell secretome analysis of reactive donors uncovered a Th1 pro-inflammatory, cytolytic and chemoattractive cytokine release profile after stimulation with rAAV2 or rAAV9 vectors. 12.4% and 9.6% of the stimulated T cells displayed a polyfunctional cytokine response, respectively, including elevated polyfunctional inflammatory indices. These responses were characterized by cytokine clusters such as Granzyme B, MIP1-α and TNF-α released in combination by single T cells. Overall, our results provide insights into adaptive immunity with rAAV vector serotypes which will be important in advancing gene therapy safety, vector selection, immunogenicity assessment and better patient selection for AAV gene therapy.